Investasi Emas Digital di Indonesia; Tinjauan Sistemik Maqashid Syariah - A'yun, Inarotul (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
This study aims to analyze the alignment of digital gold investment practices in Indonesia with Jasser Auda’s systemic Maqashid Shariah framework. It explores a conceptual shift from the classical five dharuriyyat (religion, life, intellect, lineage, and property) toward broader contemporary dimensions such as the Islamic civil society system (hifz an-nas), preservation of dignity (hifz al-‘ird), and sustainable human development. Using a descriptive qualitative approach that integrates normative and empirical analysis, the study finds that digital gold investment functions not only as a means of wealth preservation (hifzh al-mal) but also as a vehicle for advancing universal Islamic values, including economic justice, transparency, consumer protection, and community empowerment. While Sharia-compliant contracts particularly wakalah bil ujrah and murabahah commonly adhere to the principles of fiqh muamalah and support the realization of maqashid, persistent challenges include limited transparency in contract mechanisms, speculative risks arising from high price volatility, and wide bid-ask spreads that may introduce gharar. The study concludes by emphasizing the need for stronger collaboration between regulatory institutions such as OJK and DSN-MUI and enhanced public education to ensure that Islamic fintech develops in an inclusive, equitable, and ethically grounded manner, aligned with the Islamic imperatives of justice, sustainability, and communal prosperity.